PREPARATIONS BASED ON WOOD-DECAY FUNGI - E. O. Kostromina (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
There is a large variety of basidiomycetes in the world including xylotrophicfungi which pharmacological properties are scarcely studied. So they are a promising research object for pharmacology, biotechnology, medicine, and veterinary medicine. This paper considers ways to create medicines based on wood-destroying fungi, producing pronounced immune stimulating effect, antimicrobial, antioxidant, antitumor activity.